ANALISIS MUTU MARGARIN DENGAN PERBANDINGAN BAHAN BAKU MINYAK GORENG KELAPA : MINYAK GORENG SAWIT - Encik Eko Rifkowaty; Irianto SP; Budi Pratomo Sibuea; Devi Sariyanti; Shelvy Antika Sari (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2021)
Margarine is an emulsion (w/o), made from vegetable oil. This experimental consisted of three oil comparison treatments was coconut cooking oil : palm cooking oil 50:50 ; 70:30 ; and 90:10. Parameter to be estimated were water content, free fatty acids, organoleptic tests, and pair comparison tests. Based on the pair comparison test, the color attribute for the 50:50 treatment is the same as the color of margarine on the market, while the aroma and taste attribute of the three treatments are different from the aroma and taste of margarine on the market. The results of the hedonic test had the higest score is 50:50 treatment (most preferred). Based on ANOVA on the three treatments the color and aroma attributes were significantly different, while the taste attributes were not significantly different. The result of this research was found that the water content of 50:50, 70:30, and 90:10 treatments were 5.30, 6.37 and 6.95% respectively, while the free fatty acids were 1.17, 1.47 and 1.83%. The percentage of water content complies with SNI 01-3541-2002, but this is not the case for free fatty acids.